Pengungkapan Corporate Social Responsibility dan Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Moderasi - Miladeny, Ni Nyoman Mira; Damayanthi, I Gusti Eka Ayu (E-Jurnal Akuntansi, 2021)
This purpose to obtain empirical evidence regarding the effect of Corporate Social Responsibility (CSR) and to determine the role of profitability in strengthening the influence of Corporate Social Responsibility on firm value. This research was conducted on consumer goods industrial companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The number of samples was 75 in 3 years of observation, with the method of collecting samples using the nonprobability sampling method with purposive sampling technique. The data analysis technique used Moderate Regression Analysis (MRA). The results of this research stated that CSR has an effect on firm value and profitability is not able to moderate the effect of CSR on firm value. Keywords : Corporate Social Responsibility (CSR); Firm Value (Tobin’s Q); Profitability (ROA).